2016
DOI: 10.1103/physrevphyseducres.12.010127
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum development in studio-style university physics and implications for dissemination of research-based reforms

Abstract: Over the past few decades, a growing body of evidence demonstrates that students learn best in engaging, interactive, collaborative, and inquiry-based environments. However, most college science classes are still taught with traditional methods suggesting the existing selection of research-based instructional materials has not widely transformed undergraduate education. SCALE-UP is a renovated pedagogy and classroom environment that has achieved a greater impact than most, used extensively throughout the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This has been attributed to instructors' preferred beliefs of what content should be covered to effectively develop conceptual understanding. Misunderstandings when transferring content from one instructor to the next also lead to differences in activities [8]. Such challenges were evident when Bobby went a different route with activities because he was unable to make sense of the CD provided.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This has been attributed to instructors' preferred beliefs of what content should be covered to effectively develop conceptual understanding. Misunderstandings when transferring content from one instructor to the next also lead to differences in activities [8]. Such challenges were evident when Bobby went a different route with activities because he was unable to make sense of the CD provided.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The full theory articulates stages of adoption that an individual experiences, characteristics of an innovation that influence adoption, prior conditions that influence adoption, and types of knowledge that support effective adoption among adoptees ( Rogers, 2010 ). This change theory has been tested repeatedly across contexts, including in STEM higher education, and has explanatory power regarding individual change (e.g., Rogers, 2010 ; Foote, 2016 ).…”
Section: Change Theory and Theory Of Changementioning
confidence: 99%
“…Along the same lines, Lasry et al [8] found that an instructor's teaching methods are more important than the format of their room, such that teacher-centered pedagogies enacted in student-centered classrooms may have negative effects on students who have low physics knowledge prior to taking the course [8]. Furthermore, a recent study by Foote [9] found that even when the instructors adopting SCALE-UP have an interest in physics education research (PER) and are motivated to make the reform, difficulties in implementation of the researchbased instructional material designed for SCALE-UP can lead to instructors creating their own materials which have the possibility of not being grounded in PER outcomes and thus may not fully support the SCALE-UP reforms. Ultimately, an increasing body of evidence supports the conclusion that building a studio-mode physics classroom and conducting class within it is not sufficient to make the implementation successful; there are nuances of studio-mode physics adoption and implementation that greatly affect the impact of such a learning space.…”
Section: Introductionmentioning
confidence: 98%